2017
DOI: 10.1016/j.polymer.2017.04.033
|View full text |Cite
|
Sign up to set email alerts
|

The formation of a nanohybrid shish-kebab (NHSK) structure in melt-processed composites of poly(ethylene terephthalate) (PET) and multi-walled carbon nanotubes (MWCNTs)

Abstract: . (2017) The formation of a nanohybrid shish-kebab (NHSK) structure in meltprocessed composites of poly (ethylene terephthalate) (PET) and multiwalled carbon nanotubes (MWCNTs). Polymer, 117. pp. 208-219. Permanent WRAP URL:http://wrap.warwick.ac.uk/87613 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
1
15
1
Order By: Relevance
“…Results of stress-strain measurements are also summarized in Table 1. In contrary to the reports, on enhancement in mechanical properties for CNT-lled polyole n prepared by melt mixing [25][26][27], a fall in the mechanical properties was found for the polyethylene nanocomposites prepared by the stirring method.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of stress-strain measurements are also summarized in Table 1. In contrary to the reports, on enhancement in mechanical properties for CNT-lled polyole n prepared by melt mixing [25][26][27], a fall in the mechanical properties was found for the polyethylene nanocomposites prepared by the stirring method.…”
Section: Resultscontrasting
confidence: 99%
“…ere is no uniform "shish-kebab" morphology like our previous report [20], but it is evident that CNT is coated by PE which might restrict chain mobility. Recently, a shish-kebab nanohybrid structure was reported for polyethylene terephthalate-MWCNT composites by the melt-processing method [26]. e variation in the storage modulus with temperature was studied as shown in Figure 3 for neat PE and the polymer nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
“…CNT-induced polymer crystallisation can create nano-hybrid shish-kebab structures, induce the formation of different crystal polymorphs and alter significantly crystallisation kinetics. [34][35][36] Therefore, it is important to characterise changes in crystal structure and morphology when incorporating CNTs into polymer melts. [22] Additionally, reports have suggested modification of MWCNTs can lead to the formation of the β-polymorph of PP which leads to weaker mechanical properties and such behaviour can be studied using WAXD, [37] and scattering techniques (WAXS/SAXS).…”
Section: Functionalisation Is Essential To Overcome Van Der Waals Intmentioning
confidence: 99%
“…Several efforts have been made to regulate the crystallization rate of PET by inclusion of nanofillers [17,18]. Some authors found that SiO 2 nanoparticles [19,20], modified graphene oxide [21], multiwalled carbon nanotubes [22,23], polyhedral oligomeric silsesquioxanes [24,25] and calcium carbonate [26] could act as a heterogeneous nucleating agent and increase the crystallinity of PET.…”
Section: Introductionmentioning
confidence: 99%